2003
DOI: 10.1080/14764170310001276
|View full text |Cite
|
Sign up to set email alerts
|

The effective treatment of acne vulgaris by a high‐intensity, narrow band 405–420 nm light source

Abstract: Acne phototherapy by high intensity, narrow band 405-420 nm light is proven to be an attractive, fast, effective, non-invasive alternative to current topical and parenteral anti-acne remedies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 6 publications
2
50
1
1
Order By: Relevance
“…These patients had prolonged remission of their acne, which was evident in the eight weeks following the end of their treatment. No side effects were noted in any of the patients [42].…”
Section: Clinical Studiesmentioning
confidence: 76%
“…These patients had prolonged remission of their acne, which was evident in the eight weeks following the end of their treatment. No side effects were noted in any of the patients [42].…”
Section: Clinical Studiesmentioning
confidence: 76%
“…In the split-face double-blind selfcontrolled study, 87% of the treated sides showed more than 20% reduction of inflammatory acne lesions that remained steady at 2, 4, and 8 weeks after the end of therapy. Furthermore, no difference was noted between 8 and 12-minute treatment times (mean reduction in inflammatory lesions of 66% and 68%, respectively) [23].…”
Section: Blue Lightmentioning
confidence: 83%
“…Initial studies demonstrated that 8 weeks of blue light therapy for acne can reduce the number of inflammatory, but not comedonal, acne lesions (patients should continue a topical retinoid) [90]. Others have reported improvement of acne on the face and trunk with broadspectrum green and violet wavelengths [91].…”
Section: Radiofrequency Devicesmentioning
confidence: 99%